2012
DOI: 10.1057/ejis.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of IS architectures in French SMEs: integration approaches

Abstract: This paper, based on a cross-sectional empirical study of information system (IS) architectures within 143 small to medium enterprises (SMEs) in France, reports findings on how SMEs architect to achieve IS integration and interoperability. This research provides an empirically derived taxonomy of enterprise architectural variants of the types often described in the literature for large firms. This study finds indications that for SMEs the immediate goal of interoperability prevailed over fuller and more formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 51 publications
(37 reference statements)
1
30
0
1
Order By: Relevance
“…This model is still not generally applied, but it echoes issues currently raised by enterprises [6]. It is also aligned with the recent proposals to modify enterprise architecture concepts, like in the works from Pierre Pezziardi [7].…”
Section: Fig 2 Hub and Spoke View Of The Main French Citiesmentioning
confidence: 72%
“…This model is still not generally applied, but it echoes issues currently raised by enterprises [6]. It is also aligned with the recent proposals to modify enterprise architecture concepts, like in the works from Pierre Pezziardi [7].…”
Section: Fig 2 Hub and Spoke View Of The Main French Citiesmentioning
confidence: 72%
“…IS integration refers to the creation of some sort of linkage between two or more previously separated ISs (Markus, 2000), which has great relevance in determining M&A success (Benitez-Amado & Ray, 2012). Bidan et al (2012) propose four approaches to achieve IS integration, including Data warehousing, Enterprise Resource Planning (ERP) systems, Enterprise Application Integration re-architected systems, and application programming interface. The degree of linkage can be differentiated between loose and tight integration (Themistocleous & Irani, 2002).…”
Section: Is Integrationmentioning
confidence: 99%
“…This strategy requires some form of technical linkage between the acquirer's IS and the target's IS. This can be realized in through several approaches as outlined by Bidan et al (2012). The third proposed strategy is IS renewal.…”
Section: Is Integrationmentioning
confidence: 99%
“…As some research has already focused on how to bring EA to SMEs in general (Bernaert et al 2013b;Bidan et al 2012;Wißotzki and Sonnenberger 2012;Aarabi et al 2011;Bernaert and Poels 2011;Jacobs et al 2011), the value of the current research lies in the fact that, to our knowledge, CHOOSE is the first effort to actually develop an EA approach specifically adapted to the SME context. The present paper will elaborate on the design of the CHOOSE metamodel.…”
mentioning
confidence: 99%
“…Due to their resource poverty, SMEs experience even more difficulties than larger enterprises in employing EA experts or hiring external consultants (Kroon et al 2012). Yet, as some studies have confirmed, they may encounter several problems if they fail to implement EA (Bidan et al 2012;Bhagwat and Sharma 2007). Bernaert et al (2013b) did an extensive problem analysis of EA and SMEs and proposed the concept of EA as a good solution to be used for SMEs to solve problems related to a lack of structure and overview.…”
mentioning
confidence: 99%